SCIENTIFIC NOMENCLATURE OF MEDICAL TERMS AND ITS LINGUISTIC FEATURES (SCIENCE TIME JOURNAL, 2026)
The scientific nomenclature of medical terms represents a highly systematized layer of language that bridges medicine, linguistics, and international communication. This study investigates the structural, semantic, and functional properties of medical terminology with a particular focus on its linguistic features. Drawing on a comparative corpus of English, Russian, and Uzbek medical terms, as well as classifications presented in Scopus-indexed literature, the research highlights how medical terminology develops through processes of word-formation (affixation, compounding), borrowing (primarily from Latin and Greek), and semantic specialization. The findings indicate that medical terms function not only as precise designators of scientific concepts but also as carriers of cultural and historical layers of medical knowledge. For example, classifications distinguish between monosemantic terms (e.g., appendicitis), multivalent terms (e.g., shock), and hybrid internationalisms (e.g., bronchitis), reflecting both universality and linguistic diversity across professional discourse. The study also reveals the prevalence of terminological synonymy, with 12–15% of medical terms existing in synonymous pairs or series, which raises challenges for standardization yet enriches scientific communication.